Plant Quality of Swietenia mahagoni L. Jacq. Produced in Substrate Inoculated With Arbuscular Mycorrhizal Fungi - Falcón Oconor, Emir (2021)
[Introduction]: The mycorrhizal association is a nutritional strategy that some plants and mushrooms have developed that assures them a mutual benefit. [Objective]: To evaluate the effect of the use of arbuscular mycorrhizal fungi strains (AMF) in the growth and quality of Swietenia mahagoni L. Jacq. seedlings produced with organic substrates. [Methodology]: An investigation was conducted at the Forestry Technology Study Center of Guantánamo University from January to April 2019. A complete random block design was utilized to study the combinations of two factors: two substrates (cocoa husk + coconut fiber + pine sawdust in proportions 6:2:2 and 2:6:2) and AMF strains (Glomus cubense, Rhizophagus intraradices, Funneliformis mosseae and without inoculation). Seedling total height, stem diameter, leaf area, aerial and root dry biomass, height/diameter ratio, Dickson Index, mycorrhizal colonization, and a quality index were utilized as response variables. [Results]: Significant interactions for all variables studied were determined (p ≤ 0,001) among the studied factors. There was a differentiated effect of the mycorrhizal in the growth of Antillean mahogany seedlings. The mycorrhizal strains Glomus cubense, Rhizophagus intraradices, and Funneliformis mosseae, in the second substrate (60 % coconut fiber), promoted a significant growth increase and a major seedling quality. [Conclusions]: The effect of the mycorrhizal association in the production and quality of Swietenia mahagoni seedlings is evident for the establishment of plantations.